Chicken soup for the soul : shaping the new you : 101 encouraging stories about dieting and fitness-- and finding what works for you - Canfield, Jack, 1944-; Hansen, Mark Victor; Newmark, Amy. (Cos Cob, CT : Chicken Soup for the Soul Pub., 2010)
A collection of 101 true personal stories from regular people about dieting and fitness.
2
Keywords: Reducing diets -- Literary collections; Physical fitness -- Literary collections; Health -- Literary collections; Reducing diets -- Anecdotes; Physical fitness -- Anecdotes; Health -- Anecdotes